Environmental Management as a Key Competitive Advantage of Enterprises of a Non-Industrial Economy on The Example of The Compony «Timberland» ("Journal "U". Economy. Management. Finance.", 2019)
The article discusses the key advantages of introducing environmental management in the activities of companies. The analysis of the success of the implementation of this system in large foreign companies on the example of the leader of the footwear market “Timberland” was carried out. The data on existing programs introduced by the company to reduce natural pollution and reduce production costs by using recycled materials, and their impact on brand loyalty are presented.
Keywords: environmental management; competitive advantage; environmental protection; cost reduction; brand; Timberland